Implementasi Manajemen Sarana dan Prasarana di Pesantren: Studi Kasus Dayah Terpadu Al-Muslimun Lhoksukon Aceh Utara - Sari, Ratna Maya; Salabi, Agus Salim (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2022)
Adequate and standardized educational facilities and infrastructure are important factors in supporting the success of the learning process in classroom and educational programs in dorms. Therefore, it is important for dayah managers to pay more attention to the management and maintenance of facilities to be used optimally and contribute to improving the quality of education. The purpose of this study is to describe the practice of facilities and infrastructure management in Dayah Terpadu Al-Muslimun Lhoksukon North Aceh. The method used in this research is qualitative descriptive. The data collection techniques used are observation, interview, and documentation. The research subject is the head of facilities and infrastructure. The results of this study explain that Dayah Terpadu Al-Muslimun has carried out facilities and infrastructure management activities, including conducting needs analysis and planning, procurement, distribution, maintenance, inventory, and disposal. The effective and efficient implementation of facilities and infrastructure has implications for increasing efficiency in time and energy, learning quality, student motivation, parental involvement in education, and the image of the dayah in the community.